إمكانية انتقال المؤسسات الجزائرية للاقتصاد الدائري: دراسة ميدانية في المنطقة الصناعية لولاية برج بوعريريج. - عادل, فاطمة الزهراء (جامعة الوادي - University of Eloued, 2021)
يعد الاقتصاد الدائري نموذج اقتصادي جديد بديل عن الاقتصاد الخطي من خلال اعتماده على غلق حلقات الانتاج ورسكلة مخلفاتها بعد عملية الاستهلاك . ان الحكومات والمؤسسات ملزمة بتبنيه من خلال اعتماد استراتيجيات اقتصادية مختلفة وكذا نماذج أعمال ترتكز على مفهوم الدائرية في الانتاج والاستهلاك. في الجزائر تعد المؤسسات الانتاجية في المناطق الصناعية بولاية برج بوعريريج قطبا انتاجيا صاعدا وحتى تتمكن من الاندماج في الاقتصاد الدائري لابد لهاته المؤسسات من التحول الى استخدام الاساليب الانتاجية الحديثة الدائرية. من خلال هذا البحث سنحاول تحديد اهم الاستراتيجيات الانتاجية الدائرية التي تتبناها هاته المؤسسات، والوقوف على اهم الصعوبات والمعوقات التي تواجه المؤسسات في مسارها نحو التحول الى الاقتصاد الدائري. The circular economy is considered as a new economic model and an alternative one to the linear economy, that leads governments and firms to adopt various economic strategies circular business models based on the concept of circularity in production and consumption to be conform with it . To determine to what extent Algerian companies are willing to integrate into the circular economy, we conducted a field study in the industrial zone of the wilaya of Bordj Bou Arreridj, and we used the qualitative approach and the semi-structured interviews tool to a group of companies. in this region. From the research results, we concluded that there are technical and administrative barriers that prevent these companies from adopting circular production strategies, which requires addressing them through a set of procedures and measures within of the company and its external environmen
The potential of Algerian companies to shift to a circular economy Borj Bouaririj industrial area, an empirical stud
مقال
Keywords: اقتصاد دائري ; خطي ; استراتيجيات ; الجزائر ; برج بوعريريج